Compliance and patterns of iron-folic acid intake among adolescent girls and antenatal women in rural Tamil Nadu - Kalaiselvi Selvaraj; P Arumugasamy; Sonali Sarkar (Wolters Kluwer Medknow Publications, 2017)
Background: Anemia continues to be a major public health problem in India despite its long-recognized negative impact on health, especially of women. In a scenario where there is little increase in Hb levels even with implementation of various iron supplementation program apart from compliance, their dietary pattern also may play a role. Moreover, majority of the current literature assessed compliance to Iron Folic Acid (IFA) supplements in facility based settings. Objectives: This study aims to identify the compliance to Iron Folic Acid intake and dietary pattern which could influence the absorption of iron among anaemic pregnant women and adolescent girls in a rural area of Tamil Nadu. Methods: This community based cross sectional study was carried out in one of the primary health centres (PHC) in Tamil Nadu during the period of Feb-Mar 2013 among pregnant women and adolescent girls. From the eligible pregnant women and adolescent girls, information regarding socio economic characteristics, practices related to personal hygiene, dietary patterns, consumption of Iron Folic Acid tablets, and reason for non compliance were collected using structured questionnaires during house-to-house visit. Following this, Haemoglobin was estimated among all study participants. Results: Totally 147 (99.3%), 99 (56.6%) pregnant women, adolescent girls were found to be anemic respectively. Out of these, Iron folic acid tablets were consumed by 136 (91.9%), 60 (60.6%) of pregnant women and adolescent girls respectively. Around 90% of the anemic participants consumed IFA tablets during the night time, immediately after food in rice based diet. Pregnant women who were in their third trimester (OR 0.27, 95% CI: 0.10 to 0.69) and high socio economic status (OR 0.10, 95% CI: 0.02 to 0.55) had significant poor compliance compared to women in second trimester and low socio economic status respectively. Among the adolescent girls, increasing age and current school going status had facilitated the consumption of more number of IFA tablets. Conclusion: In this backward district, prevalence of anemia among pregnant women and adolescent girls were extremely high. Compliance to IFA tablets among pregnant women is favourable whereas among adolescent girls is extremely poor. Some of the dietary practices followed in this region could impair the iron absorption level and treatment effect.